2019
DOI: 10.1002/jaba.545
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods to teach foreign‐language targets to young children

Abstract: Using instructional strategies based on derived relational responding (DRR) to teach foreignlanguage targets may result in emergent, untrained foreign-language relations. One benefit of using DRR instructional strategies is the efficiency with which an individual acquires additional stimulus relations as a result of emergent responding following acquisition of one or a small number of relations. In the current study, we compared the efficiency of tact training alone to a traditional foreign-language teaching s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 26 publications
0
26
0
3
Order By: Relevance
“…One limitation of this study is that we did not implement within‐subject replications (i.e., we only taught one set of stimuli to mastery in each condition), and neither did previous studies on the topic except for Matter et al (2020). Within‐subject replications would strengthen experimental control by ensuring that the optimal procedure is identified for each participant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of this study is that we did not implement within‐subject replications (i.e., we only taught one set of stimuli to mastery in each condition), and neither did previous studies on the topic except for Matter et al (2020). Within‐subject replications would strengthen experimental control by ensuring that the optimal procedure is identified for each participant.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature examining the effectiveness of teaching a foreign language using behavior‐analytic procedures (Cortez et al, 2020; Daly & Douvani, 2020; Davidson & O'Connor, 2019; Dounavi, 2011, 2014; Matter et al, 2020; May et al, 2016, 2019; Petursdottir & HafliĐadóttir, 2009; Petursdottir et al, 2008; Rosales et al, 2012; H. Wu & Miller, 2007; W. L. Wu et al, 2019). Overall, these studies focused on teaching a subset of skills (e.g., listener and tact responses) and probing the emergence of others (e.g., intraverbal responses) to evaluate the most effective and efficient arrangements.…”
mentioning
confidence: 99%
“…Trained relations were maintained significantly higher compared to the derived relations in Rosales et al's (2011) study, whereas May et al's (2016 research found greater maintenance of the derived relation. A more recent study by Matter, Wiskow, and Donaldson (2020), however, indicates that trained and derived relations are maintained to a greater degree following tact training compared to mixed training methods (i.e., tact, N-F, F-N, and listener training). Generalization, on the other hand, does not always occur following behavioral training (e.g., Rosales et al, 2011, probed generalization using pictures instead of objects).…”
mentioning
confidence: 91%
“…After initial full-text eligibility screening, we identified nine articles that met the criteria (Cortez et al, 2020(Cortez et al, , 2021Daly & Dounavi, 2020;Dounavi, 2014;Matter et al, 2020;May et al, 2019;Petursdottir & Hafliđadóttir, 2009;Petursdottir et al, 2008;Wu et al, 2019). We then conducted reference and citation searches using Google Scholar and Web of Science.…”
Section: Literature Search Proceduresmentioning
confidence: 99%
“…1 PRISMA chart showing systematic literature search sequence (Page et al, 2021) the meta-analysis because it did not contain any within-subject evaluations of training conditions. In addition, we excluded Matter et al (2020) and May et al (2019) because neither study compared the emergent learning outcomes following FTT with those produced by other verbal operant training procedures. As noted above, Matter et al (2020) taught all target relations in the "mixed" training condition directly, meaning they could only test for emergent relations following FTT; May et al (2019) implemented FTT only.…”
Section: Eligibilitymentioning
confidence: 99%